Pengaruh Media Interaktif Berbasis Penyelesaian Masalah Terhadap Kemampuan Berpikir Kritis Peserta Didik - Anita - Anita (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
This study aims to determine the effectof problem-solving based interactive media on students’ critical thinking skills. The research method used is the experimental method one group pretest posttest. Data collection in this study using a test instrument. The population in this study is SMA Negeri 9 Tanjung Jabung Timur as many as 150 students. The sample used is 30 students. The results of the study indicate that there is an effect of problem solving based interactive media on student’ critical thinking skills with a significance of 0.000.